High school student’s perception of contents related to alcohol and marijuana consumption on social networks - Montero-Domínguez, Félix Ángel (Universidad Autónoma de Tamaulipas, 2018)
Social networks are virtual spaces in which millions of teenagers around the world communicate freely about themes relevant to their development and entertainment. International literature indicates that constant exposure to social networks’ content related to alcohol and marijuana consumption contributes to the development of a more tolerant perception of drugs and their use. The aim of this qualitative study was to explore the perceptions of high school students regarding the alcohol and marijuana consumption posts on social networks in a sample of 35 high school students. Four focus groups were conducted with a sample of high school students from the city of Xalapa, Veracruz. Participants were both males and females whose ages ranged between 15 and 19 years and had different scio-economic backgrounds. The focus groups verbatim was transcribed and analyzed using a grounded theory approach. Results they indicated that the content posted on social networks was participants’ main source of information about the effects and availability of alcohol and marijuana, surpassing television, teachers and parents. The online content was perceived as an extension of the peer pressure teenagers experienced to start using  drugs.